Factors affecting the status of continuing nursing education in Sindh (Pakistan) - Gonsalves, Antoinette (1998)
It is argued that continuing nursing education (CNE) is one of the main factors that prevent obsolescence in nursing practice. The review of available literature has emphasized the importance of CNE and identified factors that enhance and deter participation in CNE in developed countries such as age, position, education, time, cost etc. In addition, research in CNE has identified the need for professionals to acknowledge CNE as a way of life. Hence the intent of this study was to see if the same holds true in Sindh, Pakistan.The purpose of this study was to determine the status of CNE in Sindh, to identify the factors that affect participation in CNE and to explore the factors that inhibit planning and implementation of CNE in Sindh.A descriptive cross-sectional survey design was utilized. An institutional based cluster sampling methodology with a sample of 200 was determined using the formula for unmatched and cross-sectional studies. This study was conducted in private and government hospitals and schools of nursing in the province of Sindh (Pakistan). The subjects were randomly selected using a fish bowl method of selection. A total of 176 nurses and 20 directors/matrons were inteviewed in 22 hospitals. Two self designed interview guides were developed and pilot tested. The data was then analysed using descriptive (frequencies and means) and inferential statistics (chi-square and logistic regression).An 88response rate was obtained. Findings implied that variables which were not statistically significant to participation in CNE were: age, marital status, child dependency, educational preparation, years of service in the present institution, incentives, and years of experience. However, the variables that were significant related to participation in CNE were: the year nurses received their last diploma, type of institution in which they worked and self-directed learners (nurses who used the library and were regularly read nursing books).Logistic regression was used to summarize the results.
The results show that the following variables were statistically significant in the presence of each other and with participation in CNE: institution that conduct CNE; nurses who practice self directed learning (reading nursing books); reasons for participation (to give better patient care) and institutions that inform nurses about CNE programs.The enhancers that were highlighted in this study were age (young between 20-35 years), recent education attainment (1-5 years), nurses interest (informal/self-directed learners), interest/ self-directed learners and shorter working hours (36 hours/week).The reported barriers mainly related to institutional and situational issues. These included family responsibilities, transport, cost, job responsibilities, inconvenient schedule, seniority, in appropriate nomination criteria, lack of information given and inappropriate publicity of CNE in institutions, and lack of permission and leave to attend CNE.The findings indicated that there were limited CND programs available and those that were available were inaccessible to all nurses in Sindh. Due to the hierarchical structures in most organizations senior nurses were given preference and scholarship to attend CNE programs. Hence, since the study sample consisted mainly of junior nurses only 46 out of 176 nursed had participated in any type of CNE. The findings of this study suggest that the most significant factor is seniority. Despite having more opportunity to participate in CNE, senior nurses are not as motivated to attend CNE as younger nurses.Barriers to participation specifically found in Sindh could be used as a guide for planners of CNE. Limitations of this study prevent the findings from being generalized. However, it would be beneficial to replicate this study in a few years time to assess if any changes to enhancers and barriers have occurred.The results indicate that there are limited provisions of CNE programs for nurses. Hence to sustain CNE programs in Sindh it is essential that the nursing council alters the careers structure and support the local professional organiztions and institutions in their endeavours.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Education, Nursing, Continuing; Nursing education; Continuing education